Base-flow segmentation and character analysis of the Huangfuchuan Basin in the middle reaches of the Yellow River, China - Zhang, Yaru; He, Yi; Mu, Xingmin; Jia, Liping; Li, Yanlin (Frontiers in Environmental Science, 2022)
In recent years, with the deterioration of the ecological environment, runoff in the Yellow River has been decreasing. Given these phenomena, it is necessary to research the base-flow segmentation method and its characteristics. The Huangfuchuan Basin in the middle reaches of the Yellow River basin was selected as the research area. This paper calculated the base-flow with commonly used base-flow segmentation methods, including Base-flow index method (BFI), Hydrograph-separation techniques (HYSEP), and the digital filtering methods, and compared the applicability of these methods in the study area. Then the variation characteristics, abrupt change year, periodic change, and future trend of the base-flow were analyzed. The results are as follows: (1) Through the analysis and comparison of several common base-flow segmentation methods, these methods had a marked difference in base-flow segmentation. DF4 in digital filtering was the most appropriate method in the research area. (2) The flow presented a decreasing trend, and the base-flow also showed a significant decrease trend by the Mann-Kendall trend test. (3) The base-flow had periodic variations of 3-6, 7-18, and 19-32. The whole time was 31 years as the center of the periodic change, the first primary cycle of base-flow change. (4) The base-flow mutation occurred in 1986. The trend of future development is positively correlated with past change, showing a trend of continuous decrease. Selecting the appropriate method of base-flow segmentation and reasonably analyzing the variation characteristics of base-flow can provide scientific guidance for the ecological environment construction and water resource evaluation in the Huangfuchuan Basin and even the Yellow River Basin.